Meningkatan Motivasi Belajar IPS Siswa Kelas V Madrasah Ibtidaiyah Tambakreja Lakbok melalui Metode Pembelajaran Cooperative Learning Tipe Teams Games Tournament (TGT) - Nurholis; Holiludin (Insanulhaq Cidadungu Foundation, 2023)
The learning activities that are expected from a teacher are student-centered learning processes, not teacher-centered. It is the teacher's obligation and duty to ensure this because the teacher is the main actor. Thus it is hoped that through the student centered approach can increase student learning motivation which affects student achievement. This research is a class action research (classroom action research). This research is intended to improve the learning process so as to increase the learning motivation of class V MI Tambakreja. According to Suharsimi Arikunto (2006: 96) classroom action research, namely research conducted by the teacher in the classroom where he teaches with an emphasis on improving learning processes and practices. The learning motivation of the fifth grade students of MI Tambakreja has also increased. In the pre-action, the average was only 52% or very less category. Furthermore, in cycle one it increased to 65% in the sufficient category and in cycle two it increased again to 78% in the good category. Teachers must better understand how to convey material to students according to the level of student development.